Contrast-enhanced Ultrasound Imaging Following Transperineal Laser Ablation for Lower Urinary Tract Symptoms - van Kollenburg, R.A.A.; van Riel, L.A.M.J.G.; Oddens, J.R.; de Reijke, T.M.; van Leeuwen, T.G.; de Bruin, D.M. (Urology (Ridgewood, N.J.), 2025)
To describe the shape and volume of ablations created by transperineal laser ablation (TPLA) using multiple fiber configurations. Furthermore, to measure the change in the ablation zone and prostate volume over time, and to assess inter-patient ablation volume variability. Data from a prospective, single-center, interventional pilot study including 20 patients is used. All subjects underwent TPLA using the EchoLaser system, using 2 to 4 fibers, depending on prostate size and shape. Contrast-enhanced ultrasound (CEUS) was performed post-treatment and at 1 and 12 months. The prostate and ablation zone volumes were calculated on segmented CEUS imaging. The ablation zones were clearly identified on CEUS as non-perfused areas. Depending on fiber configuration, their shape varied from an ellipsoid to a clover profile. Ablation volumes varied from 0.9 (0.6-2.2)cm3 using a single fiber and 1800 J to 8.7 (3.9-19.0)cm3 (median, range) using 2 fibers and 7200 J energy per lobe at 1 month. At 12 months, the majority of the ablation zones showed a volume reduction. Median prostate volume decreased from 78 (37-145)cm3 at baseline to 46 (27-124)cm3 at 12 months (P=.0002). There was a relation between prostate volume reduction and Qmax (slope=0.18) and IPSS (slope=−0.18) improvement. This study described ablation zone shape and measured the ablation volume following TPLA by various fiber configurations using CEUS, and compared these to functional outcomes. Prostate volume reduced significantly during follow-up. Segmentation showed substantial inter-patient ablation volume variation, which limits treatment predictability and thus accuracy.